Diseases of Sweetpotato - Ogero, K.; Vlugt, R. van der. (Springer, 2023)
Sweetpotato is the sixth most important food crop globally. Whereas in developed countries like Canada, Europe, and the United States, it is considered a vegetable, it is a major staple food crop in sub-Saharan Africa. Cropping systems and varietal preferences vary between temperate and tropical countries. This influences the type of diseases encountered in temperate and tropical countries. Some diseases occur globally, but severity may differ between different regions. Viruses pose the greatest challenge to sweetpotato production globally. Sweet potato virus disease (SPVD) caused by synergistic interaction between sweet potato chlorotic stunt virus (SPCSV) and sweet potato feathery mottle virus (SPFMV) can cause between 56% and 98% yield losses. The crop is also affected by bacterial diseases such as bacterial wilt caused by Ralstonia solanacearum and Streptomyces soil rot caused by Streptomyces ipomoeae among others. Over 32 fungal diseases have been reported in sweetpotato, infecting the crop both in the field and in storage. Field fungal diseases include leaf spot and leaf petiole and stem blight caused by several species of Alternaria. Economically important storage fungal diseases include black rot, java black rot, and Rhizopus soft rot. The crop is also affected by various nematodes. The importance of sweetpotato diseases varies geographically. For instance, whereas SPVD and other viruses are economically important in sub-Saharan Africa, nematodes do not cause significant loss and do not warrant control. This chapter discusses the geographic distribution of the different diseases, their importance, and management practices.